Gamification in Education in Turkiye: Insights from Graduate Studies Conducted between 2014-2024 - Fidan, Dr. Cigdem; Pekgöz, Şeyma (International journal of educational research review, 2025)
This study investigates graduate studies on gamification in education in Turkiye to explore the field and methodology-related trends in education to examine gamification. The study adopts a qualitative approach and employs a descriptive analysis to examine graduate studies published in the National Thesis Center of Higher Education Board. 77 master’s level and 23 doctoral-level studies conducted on gamification in education in Turkiye between 2014 and 2024 were included in the study. The analysis used research methodologies, such as data collection and data analysis tools, analyzing gamification in education, subject fields in which gamification is researched, and keywords used in graduate studies examining gamification in education were identified as variables. The results indicate a diverse landscape of graduate-level research on gamification in education in Turkiye, varied by research methodologies, data collection tools, and analytical techniques across disciplines. The study suggests prioritizing underrepresented fields and expanding the use of qualitative research tools to address gaps in the existing literature on gamification in education in Turkiye.